Analisis Kesiapsiagaan Nelayan Menghadapi Situasi Darurat Bencana: Studi Literature - Yusuf Syahputra Siregar; Faisal Halim Soritaon Harahap; Abdurrozzaq Hasibuan (PT. Alahyan Publisher Sukabumi, 2024)
Fishing is also a job that carries a huge risk of danger. These disaster factors cause an emergency for fishermen. Disasters are a sign of human life that cannot be known exactly when they will occur, therefore we need to be prepared to determine the right way to deal with disaster events. The method used is a literature review to collect, identify and evaluate efforts related to emergency management that could endanger fishermen. The data source used in this research is a secondary data source, which was obtained through media publications and Google Scholar. Based on the articles that have been collected from the 11 articles analyzed, the results of the literature study analysis show that there are factors that influence fishermen's preparedness in facing disasters. All of these factors must be taken into account so that fishermen are better prepared to face disaster emergency situations, such as attitudes, knowledge and education about disasters, fishermen's readiness, disaster emergency response planning, disaster warning systems, resource mobilization are factors that influence fishermen's preparedness in facing disasters. All these factors must be considered so that fishermen are better prepared to face disaster emergency situations.